Continuous renal replacement treatment and the 'bleeding patient' - Davies, Hugh; Leslie, Gavin; Morgan, D. (British Medical Journal Publishing Group, 2010)
A women suspected of intra-abdominal bleeding with end-stage renal failure requiring maintenance haemodialysis was treated with continuous veno-venous haemodiafiltration in the intensive care unit. The use of citrate restricted to the extracorporeal circuit maintained continuity of treatment and avoided the adverse affects of systemic anticoagulation. Regional citrate anticoagulation was achieved using the 'modified' Alabama Protocol. A description of the protocol is included along with troubleshooting instructions. Violations of the protocol challenged the adequacy of workforce training and patient monitoring, which saw systemic ionised calcium level reach 0.62 mmol/litre and base deficit drop -14.7. After protocol transgressions were corrected the patient was successfully treated and satisfactory biochemical control achieved without placing the patient at increased risk of bleeding. Training and vigilance in the use of citrate is essential to maintain patient safety.